Unlocking thermodynamic enolate for kinetically controlled desymmetrizing vinylogous (4+1) carbospiroannulation - Singh, Sanjay; Singh, Abhijeet; Pandya, Rinu; Vanka, Kumar; Singh, Ravi P. (Chemistry-A European Journal, 2025)
An unprecedented thermodynamically unfavorable (4+1) deysmmetrizing spiroannulation through a thermodynamic enolate intermediate, enabling a single-step synthesis of ubiquitous scaffolds such as all-carbon chiral spirocycles, is disclosed. In this spiroannulation, we present a vinylogous organocatalytic enantioselective desymmetrizing (4+1) cycloaddition approach involving alkylidene malononitrile and cyclopent-1,3-dienone. This carbospiroannulation method produces functionally enriched spiro[4,4]nonane structures with three stereocenters, has presented good-to-high yields and enantiomeric ratios. Detailed DFT calculations reveal an intriguing reaction mechanism, which validates our observations.
Keywords: 3-diones; alkylidene malononitrile; cyclopent-1; quaternary stereocenters; spiro compounds; thermodynamic enolate